Analysis of Pre-Service Teacher’s Performance Viewed by Creativity and Self-Regulated Learning - Sarjana, Ketut; Kurniawan, Eka; Lu’Luilmaknun, Ulfa; Kertiyani, Ni Made Intan (Jurnal Kependidikan, 2023)
This study aims to analyze the effect of creativity and self-regulated learning on the pre-service teacher’s performance in school internships. This research was an ex-post facto with a quantitative approach. The sample of this research was selected using a purposive sampling technique. Seventy-three students at the University of Mataram FKIP participated in the school internship as the research sample. The research instrument used was a creativity questionnaire, a self-regulated learning questionnaire, and a school internship performance instrument. The data obtained were analyzed using multiple linear and straightforward linear regression tests. The results of this study were a) there was a significant effect between creativity and self-regulated learning on the performance of the pre-service teacher in school internship, b) there was a significant influence between creativity and pre-service teacher performance and c) there was a significant effect between self-regulated learning and pre-service teacher performance. This study concludes that there is an influence, either partially or simultaneously, between creativity and self-regulated learning on the performance of pre-service teacher who takes school internship programs. It implies that creativity and self-regulated learning are two aspects to consider when evaluating PLP student performance. Improving their abilities in these two areas will help them succeed in the PLP program.